Resilience and food security: rethinking an ecological concept. (19th June 2017) - Bullock, James M.; Dhanjal‐Adams, Kiran L.; Milne, Alice; Oliver, Tom H.; Todman, Lindsay C.; Whitmore, Andrew P.; Pywell, Richard F.
Summary: Focusing on food production, in this paper we define resilience in the food security context as maintaining production of sufficient and nutritious food in the face of chronic and acute environmental perturbations . In agri‐food systems, resilience is manifest over multiple spatial scales: field, farm, regional and global. Metrics comprise production and nutritional diversity as well as socio‐economic stability of food supply. Approaches to enhancing resilience show a progression from more ecologically based methods at small scales to more socially based interventions at larger scales. At the field scale, approaches include the use of mixtures of crop varieties, livestock breeds and forage species, polycultures and boosting ecosystem functions. Stress‐tolerant crops, or with greater plasticity, provide technological solutions. At the farm scale, resilience may be conferred by diversifying crops and livestock and by farmers implementing adaptive approaches in response to perturbations. Biodiverse landscapes may enhance resilience, but the evidence is weak. At regional to global scales, resilient food systems will be achieved by coordination and implementation of resilience approaches among farms, advice to farmers and targeted research. Synthesis . Threats to food production are predicted to increase under climate change and land degradation. Holistic responses are needed that integrate across spatial scales. Ecological knowledge is critical, but should be implemented alongside agronomic solutions and socio‐economic transformations. Abstract : We define resilience in the food security context as maintaining production of sufficient and nutritious food in the face of chronic and acute environmental perturbations . In agri‐food systems, approaches to enhancing resilience show a progression from more ecologically based methods at small scales to more socially based interventions at larger scales. Holistic responses are needed that integrate across spatial scales.